2021
DOI: 10.1111/1469-8676.12988
|View full text |Cite
|
Sign up to set email alerts
|

A lesser human? Utopian registers of urban reconfiguration in Maputo, Mozambique

Abstract: In the age of climate change, human life’s pliability is also re‐shaping anthropological debates. For debates centring on the urban domain, questions revolve around flexibility, adaptability and resilience, while in work drawing on the Anthropocene similar ideas of human beings as subsumable to Gaia are emerging. This article reflects on how these perspectives interweave and imply a paradoxical human figure. On the one hand, they convey a being that simultaneously infuses, consumes and transmogrifies the world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…I have suggested that the concept of permanent impermanence usefully describes the affective state and way of being in the world that results from a particular ordering of im/mobilization patterns along spatial and temporal dimensions. Referring to emergent dynamics of expulsion and exclusion, it signals the production of a new class of guest workers characterized by a heightened plasticity and pliability-a lesser human (Bertelsen, 2021)-in economic systems organized around seasonality or other forms of temporally circumscribed labor and (directly or indirectly) forced migration (e.g. through the denial of access to citizenship or the impossibility of settling down).…”
Section: Discussionmentioning
confidence: 99%
“…I have suggested that the concept of permanent impermanence usefully describes the affective state and way of being in the world that results from a particular ordering of im/mobilization patterns along spatial and temporal dimensions. Referring to emergent dynamics of expulsion and exclusion, it signals the production of a new class of guest workers characterized by a heightened plasticity and pliability-a lesser human (Bertelsen, 2021)-in economic systems organized around seasonality or other forms of temporally circumscribed labor and (directly or indirectly) forced migration (e.g. through the denial of access to citizenship or the impossibility of settling down).…”
Section: Discussionmentioning
confidence: 99%
“…Many thanks to Ruy Blanes and Bjørn Enge Bertelsen for their response to my critique (Bråten 2022a) of their special section on 'Utopian Confl uences' (especially, Blanes and Bertelsen 2021;Bertelsen 2021), and to Social Anthropology/Anthropologie Sociale for publishing the exchange. Th e theoretical questions that arise from our diverging stances are, hopefully, of general interest.…”
Section: Final Replymentioning
confidence: 99%
“…Such critical discussions about futurelessness as a figuration of (political) time are not, of course, solely the domain of irreconciliation or event studies. Building on Frantz Fanon, Achille Mbembe's (2017) critique of both capitalism and racism in an age of the Anthropocene (see also Bertelsen 2021) analyses a thoroughly fragmented subject which Mbembe recognizes as becoming globally common. Centrally, his notion of the ‘becoming black of the world’ seems to indicate the cancelling of the future in a world that is blackened, as it were, by the violence of Anthropocenic politics.…”
Section: Irreconciliation Time and Justice: Repurposing Uncontained V...mentioning
confidence: 99%